SIMULATION METHOD FOR MEASURING THE IMPACT ENERGY OF RAIL VEHICLES EQUIPPED WITH A SOFT ABSORBER - Aleksandra LISOWSKA; Henryk SANECKI; Maciej SZKODA (Transport Problems)
This paper presents a simulation method for testing the energy absorbed by the absorption systems of rail vehicles equipped with a soft absorber. The method makes it possible to verify the actual behavior of the absorption system during the impact of two vehicles. The first part of this paper describes the structural elements of a railway vehicle performing the function of an energy absorber during an impact according to the EN 15227 standard. A soft absorber, the so-called honeycomb, is analyzed in detail. It is a multicellular structure often used in rail vehicles due to its properties of controlled deformation. The literature review describes the research conducted on this element. The analytical part of this paper describes a general mathematical model of a rail vehicle collision according to Scenario 1, in which the collided vehicles are of the same type, and Scenario 2 for vehicles of different types. A computational impact simulation for the two scenarios has been carried out using the specialist software Mathcad, and the results are presented in graphs. The paper ends with conclusions presenting the application possibilities of the developed tool.